Foreign Language Speaking Anxiety: A Systematic Review of A Decade in South East Asia - Sepa Phalosa Ady, Rizky; Mardiah, Zaqiatul (Universitas Cokroaminoto Palopo, 2024)
Over the past decade, at least more than 2.500 studies on Foreign Language Speaking Anxiety (FLSA) in the context of English as a Foreign Language (EFL) have been conducted over the globe. While English serves as a lingua franca (Alptekin, 2012), the research outcomes concerning FLSA towards English conducted by researchers worldwide cannot be universally generalized across all languages. This systematic review aims to examine the studies, processes, and findings regarding FLSA for non-Latin languages Other Than English (LOTE) popular in South East Asia (SEA), including Arabic, Mandarin, Japanese, and Korean. The review identified a total of 18 journal articles published in four countries (Malaysia, Indonesia, Thailand, and the Philippines), with most studies conducted in higher education settings using quantitative methods, predominantly cross-sectional. Findings reveal that students in SEA continue to experience moderate to high levels of FLSA, primarily attributed to Fear of Negative Evaluation (FNE) by peers and Communication Apprehension (CA). Additionally, negative correlations and positive influences of variables such as Achievement, Willingness to Communicate (WTC), Motivation, Humor, Online Classes, and Teacher Behavior on FLSA have been explored. Despite the comprehensive review, there are still significant gaps and wide-ranging potential for further research, including FLSA studies in other SEA countries, as well as investigations into non-conventional formal settings such as language courses and contemporary platforms like Video Chat Platform, Language exchange app, and AI Assistant.